Application of SWOT-AHP in analyzing external and internal environment of youth empowerments. Issue 1 (March 2020) - Syamsuddin, A P; Ridwan,; Supratman,
Abstract: The low quality of youth resources, the lack of optimal coordination between youth organizations and youth empowerment in Soppeng District so that researchers are interested in conducting more in-depth studies. This study aims to analyze strengths, weaknesses, opportunities, and threats in the implementation of youth empowerment programs and formulate strategies for implementing the Soppeng District Youth and Sports Service Youth Empowerment Program. This study uses the SWOT-AHP method with the descriptive translation then tabulated so as to give birth to a choice of strategies that are a priority or more important. The results of the study found that the strength (S), weakness (W), opportunity (O) and threat (T) groups in the four groups were higher (S) with a value of 0.4958 compared to weaknesses, opportunities, and threats, for threats with the lowest value is 0.0719. The global priority of 16 statements from each strength (S), weakness (W), opportunity (O) and threat (T), the highest value is a 0.5300 statement of weakness (W1) while the lowest value is a threat (T4) 0.0609. The priority groups that are the focus of strengthening the Soppeng District Dispora include the highest value of the SWOT group (Strengths, Weaknesses, Opportunities, and Threats) while the factors that have the highest common values are (Weakness, Opportunity, Threat and Strength). The implementation of the youth empowerment strategy program in Soppeng Regency run by the Dispora is inseparable from the influences of various aspects, both from strength and weakness (internal) and Opportunities and Threats (external). But the choice of the right strategy for Dispora or things that need to be strengthened from the four strategies ST1, ST2, ST3 and ST4, namely ST1 (SO). Awaken young people about the importance of empowerment can be carried out through seminars and provide training on the importance of empowerment, but the youth as objects and subjects must be aware of themselves that the future will be a legacy for them as a youth, especially youth in Soppeng Regency.